REGULATING RELIGIOUS HETERODOXIES IN CONTEMPORARY INDONESIA - Ropi, Ismatu; Wahid, Din (Peminat Ilmu Ushuluddin, 2024)
This article delves into a discussion about how the Indonesian government, specifically the Ministry of Religious Affairs (Kemenag RI), regulated the handling of problematic religious movements and groups in Indonesia in 2017. It also aims to investigate whether the 2013 fatwa issued by the Indonesia Council of Ulama (MUI), which consists of religious scholars and holds significant influence, played a pivotal role in shaping this regulatory framework. Both of these documents were issued in response to the actions of individuals and groups that were perceived to have crossed the line of acceptability or violated the core beliefs of mainstream religious groups in Indonesia. They both outline key principles aimed at preventing any activities, teachings, or movements that strayed beyond the boundaries of legitimate dissent and encroached upon the sacred aspects of religion. In essence, the primary theme running through both documents is the preservation of mainstream religious orthodoxy. This reflects the government's and the dominant religious group's efforts to control and closely monitor any groups that appear to deviate from mainstream beliefs. The government and the majority religious community are viewed as the protectors of orthodoxy, and they are unhesitant in restricting individuals or groups accused of being